IJCM_332A: Factors affecting quality of life among antenatal women seeking health care in tertiary care hospitals of Mangaluru - Mithra Prasanna; Bhat Mayur K; Priyanka N P; Bavihalli Rohit S; Yatheesh; Ayesha (Wolters Kluwer Medknow Publications, 2024)
Background: QOL is defined as "individuals' perception of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns." Pregnancy is a physiological state associated with several emotional and physical changes, and the antenatal period is the moment of preparation of the woman for the childbirth and maternity. Thus, poor quality of life can have adverse effects on mother and the fetus. In order to develop methods to improve the quality of life of pregnant women, the factors affecting it should be understood; and our study aims at providing such understanding. Methodology: A hospital based Cross-sectional study of the pregnant women seeking antenatal health care in Government Lady Goschen Hospital and KMC, Attavar. The data collection was done from 14-03-16 to 31-03-16 using a questionnaire consisting of 4 parts-participant details, WHO QOL- BREF, QIDS and modified Kuppuswamy scale. Results: The study was done among 195 pregnant women, and the mean QOL-BREF score was found to be 73.60. 60.5% participants belonged to lower socioeconomic status, and had a lower QOL in physical, psychological and environmental domains. 54.6% participants showed symptoms of depression and had a lower QOL in physical domain. Other factors like parity, history of abortion and complications in the current pregnancy did not show a significant association with QOL score. Conclusion: The QOL of antenatal women seeking health care in tertiary health care setup was found to be good. The factors that significantly affected the quality of life were depression and lower socio-economic status. They had a negative impact on the quality of life.